Early life microbial exposure, child neurocognition and behaviour at 2 years of age: A birth cohort study - Senn, E; Symeonides, C; Vuillermin, P; Ponsonby, A (Wiley, 2019)
Aim: To investigate the relationship between factors which influence external microbial exposures (FEMEs), previously identified to be protective or to increase the risk of the development of allergic disease, and cognition and behaviour in infants 2 years of age in an Australian population.